Skills Assessment of Medical Personnel Information at Puu’weri Health Center in Waikabubak City - Eriska Haning; Devliany Doke (JURNAL KESEHATAN PRIMER, 2018)
Background: One problem that often results in patient dissatisfaction is communication between health workers and patients, including services available at First Level Health Facilities (FKTP). 35-40% of patients were dissatisfied with the consultation and information received from their doctors. The doctor's limitations are on impatience listening to patient complaints, limited knowledge or information and rigidity in conveying that information to patients. Research purposes: To analyze medical personnel's informational skills at the Puu’weri Health Center First Level Health Facility based on the perspective of service users. Method: descriptive analytical method with cross sectional design with a survey using a questionnaire. The population in this study were patients who used the services of Puuweri Health Center. The sample in this study was 184 patients. Results: Informational skills of medical staff at the Puuweri Health Center in Waikabubak City 79.3% of patients who use PuuWeri Health Center health services correctly answer the keywords of the informational skills. And 79.3% have sufficient knowledge to access information. And as many as 57.6% of patients who use health services find out about the Human Resources (HR) in the Puskesmas and then will utilize the services offered. Suggestion: medical staff can improve their ability to provide health so that it has an impact on the quality of health services provided by Puu’Weri Health Center.